Síntese e propriedades da zeólita faujasita nanométrica aplicada à catálise básica - Vicente, João Guilherme Pereira (2015)
In order to increase accessibility to catalytic sites, several studies currently aimed at reducing the diameter of the particles of zeolites to the nanometer scale. So, the increase in aging temperature caused a reduction in the size of the particle to 40 ° C, higher values for the phenomenon of crystal growth has become prevalent. At temperatures between 50 ° C and above, evidenced the formation of materials with relative crystallinity, even before the hydrothermal treatment step. On aging at 60 ° C for 24 h, according to the XRD patterns and the use of the Scherrer equation was obtained the smaller crystallite sizes of all the syntheses performed, those having dimensions of about 12 nm and particle of 300 nm. Thus, when the synthesis time compared to the literature, there obtained a reduction of 54 h and no more necessary to make the hydrothermal treatment step at 100 ° C. To evaluate the influence of the size of the zeolite crystals, when they apply the basic catalysis, using the commercial and nanometric zeolites synthesized. Both materials modified by ion exchange with ammonium cations and methylammonium, in order to generate catalytic sites with strong basic properties. Due to steric hindrance ion exchange not completely occurred, however the nanometric zeolite showed values of ion exchange higher for all cations used for commercial zeolite, except for the tetramethylammonium cation, where the results were equal. Among all exchangers used cations, zeolites containing methylammonium had better conversions. The catalytic evaluations conducted have shown overall prevalence of catalysts with nanosized front of commercial micrometric zeolite. The greater accessibility and better diffusion of the reactants and products through the pores of zeolites with nanosized crystallites provided better performance in catalytic studies on activity, kinetics, reaction rate, activation energy and TOF.